Elevated plasma concentration of IP-10 in patients with type 2 diabetes mellitus - SATO, Hiroshi; NAKAYAMA, Kenji; XU, Honglan; SUGIURA, Akira; OGAWA, Susumu; ITO, Sadayoshi; SATO, Toshinobu; KATO, Taro (Nihon Jinzo Gakkai shi, 2005)
Recent studies have shown the important role of proinflammatory cytokines and chemokines in the pathogenesis of atherosclerosis and diabetes mellitus (DM). Interferon-inducible protein of 10kD (IP-10/CXCL 10), a member of the C-X-C chemokine superfamily, is a potent chemoattractant for activated T lymphocytes and is reported to be involved in various disease states including atheroma plaque formation, inhibition of tumor angiogenesis and maintenance of podocyte function. However, the involvement of IP-10 in type 2 DM, especially in its vascular and renal complications, is largely unknown. To elucidate the etiopathological role of IP-10 in type 2 DM, we measured the concentrations of IP-10 together with IFN-γ, TNF-α, IL-18, IL-6 and MCP-1 in plasma samples from 103 type 2 DM patients with various degrees of nephropathy. A significant difference in the plasma level of IP-10 was observed between the patients and the control subjects (183.3±12.5pg/ml vs 65.6±9.3pg/ml, p<0.05). IP-10 correlated IL-18, IL-6, TNF-α and MCP-1. The IFN-γ level was below the detectable range. IP-10 levels became higher with the progression of nephropathy: IP-10 levels were 148.9±14.5, 174.2±17.2 and 231.9±31.3pg/ml in patients with an urinary albumin creatinine ratio of <30, 30 to 300 and >300μg/mg Cr, respectively. Similarly, IL-18, IL-6, MCP-1 and TNF-α levels in patients with overt albuminuria were significantly higher as compared with those without albuminuria (IL-18, 367.3±45.6 vs 203.5±17.6pg/ml; IL-6, 1.61±0.26 vs 0.87±0.13pg/ml; TNF-α, 1.83±0.48 vs 0.61±0.07pg/ml; p<0.05, respectively) in consistent with previous reports. These results suggested that IP-10 may have an etiopathogenic role in type 2 DM and diabetic nephropathy as one of the downstream effectors of proinflammatory cytokines.